2021
DOI: 10.1186/s42269-021-00550-w
|View full text |Cite
|
Sign up to set email alerts
|

Review of a controversial treatment method in the fight against COVID-19 with the example of Algeria

Abstract: Background As of April 23, 2021, more than 145 million cases and almost 3.07 million related deaths were noted because of the coronavirus (Covid-19) Pandemic. Considering the low rate vaccination, the alternative that divided opinions for a long time is an old medicine called hydroxychloroquine. Main body The aim of this review was to synthesize the different highlights of the most important studies published since the beginning of the epidemic cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In some cases, CQ is also used as a steroid-sparing agent in severe asthma patients [ 96 ], suggesting no major harm of these medications in asthma. Although there are studies confirming that CQ and HCQ have antiviral activity on SARS-CoV-2 in vitro [ 97 ], the effectiveness of these synthetic molecules and these being devoid of toxicity are still questioned by a portion of the scientific community [ 98 ].…”
Section: Impacts Of Asthma In Covid-19 Infestationmentioning
confidence: 99%
“…In some cases, CQ is also used as a steroid-sparing agent in severe asthma patients [ 96 ], suggesting no major harm of these medications in asthma. Although there are studies confirming that CQ and HCQ have antiviral activity on SARS-CoV-2 in vitro [ 97 ], the effectiveness of these synthetic molecules and these being devoid of toxicity are still questioned by a portion of the scientific community [ 98 ].…”
Section: Impacts Of Asthma In Covid-19 Infestationmentioning
confidence: 99%
“…Based on certain inconclusive studies and research, desperate measures were incorporated in the form of resilient drugs like Hydroxychloroquine and Remdesivir, which however were not of much significance in combating the pandemic (Khuroo 2020 ). A recent report showed that hydroxychloroquine treatment significantly lessens viral load/disappearance in COVID-19 patients if given with azithromycin (Gautret et al 2020 ; Aouissi et al 2021 ). A study by Grein et al ( 2020 ) supported the compassionate use of remdesivir for clinical improvement in COVID-19 patients.…”
Section: Strategies For the Effective Management Of The Pandemicmentioning
confidence: 99%
“…During February and March 2020, Algeria likely received the highest number of imported COVID-19 cases from Europe, compared to any other African country (Sun et al, 2020). The COVID-19 pandemic emerged in Algeria through imported cases from Italy, France and Spain (Daw et al, 2020), with the first case detected on February 25, 2020 (Ababsa & Aouissi, 2020;Aouissi et al, 2021). Since then, Algeria has been hit by three waves of COVID-19 (World Health Organization, 2021).…”
Section: Introductionmentioning
confidence: 99%